Dinamika Post-Traumatic Stress pada Masyarakat Penyintas Bencana di Hunian Tetap Bumi Semeru Damai (BSD) - Ahmad Faisol; Bambang Subahri (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2026)
Natural disasters in the Semeru region have resulted not only in physical destruction but also in long-term psychological consequences for affected communities, particularly in the form of Post-Traumatic Stress (PTS). Although survivors have been relocated to permanent housing, traumatic stress often persists and fluctuates during the post-relocation phase. This study aims to explore the dynamics of Post-Traumatic Stress and the factors influencing its persistence among disaster survivors living in the Bumi Semeru Damai (BSD) permanent housing complex in Lumajang. This study employed a qualitative approach using a case study design and involved four disaster survivors with diverse ages and life backgrounds. Data were collected through in-depth interviews, direct observations, and documentation, and analyzed thematically using the Conservation of Resources (COR) theory. The findings indicate that Post-Traumatic Stress among survivors is dynamic and non-linear, with symptom intensity changing over time. The persistence of Post-Traumatic Stress (PTS) is strongly associated with the loss of critical resources, while social support functions as a protective factor that facilitates psychological adaptation. These findings highlight the need for post-disaster recovery strategies that prioritize long-term psychosocial support and resource strengthening.